Exploring localization properties in a folded N x N network on a cylinder’s shape with diagonal disorder and long-range hopping - Santos Junior, M.S.; de Moura, F.A.B.F. (Physica A, 2025)
In this work, we employ the inverse power method (IPM), a well-established technique in linear algebra, to investigate the quantum dynamics of a one-electron Hamiltonian in a unique geometric setup. Specifically, we consider a two-dimensional N×N lattice folded into a cylindrical topology, incorporating diagonal disorder and long-range hopping with a power-law decay. Unlike conventional studies that consider two-dimensional planar lattices, our model explicitly incorporates the curvature of the cylindrical geometry, enabling us to examine its potential influence on electronic properties. By analyzing the interplay between disorder, long-range hopping, and the system’s intrinsic curvature, our results suggest that geometry may play a role in the localization and transport behavior of electrons. These findings provide insights into how geometric factors could affect quantum systems, with potential implications for materials science and nanostructures exhibiting curved geometries. •One-electron Hamiltonian of a system that consists of an N×N network that has been folded into a cylinder.•This system is subject to diagonal disorder and long-range hopping with a power-law decay.•The existence of extended states due to long-range hopping terms.